A short and efficient stereoselective synthesis of the polyhydroxylated macrolactone (+)-aspicillin - Dixon, D; Foster, A; Ley, S (2000)
[structures: see text] A short and efficient synthesis of the polyhydroxylated macrolactone (+)-aspicilin 1 using a stereoselective lithium perchlorate mediated addition of allyltributyltin to the equatorially disposed carboxaldehyde of 3 (derived from (R',R',R,S) butane diacetal protected butane tetrol 2) as the key step is described. Terminal group manipulation and Masamune-Roush olefination using phosphonate ester 4 followed by macrocyclization via ring closing metathesis afforded the natural product after partial hydrogenation and global deprotection.